Effects of reduction factor on rain attenuation predictions over millimeter-wave links for 5G applications - M. Rashid; Jafri Din (Bulletin of Electrical Engineering and Informatics, 2020)
Millimeter-wave will be the strong contender for the terrestrial link using for 5G networks. So it is imperative to examine these frequency bands to ensure the uninterrupted services when 5G network is connected in tropical regions. A critical challenge of link-budgeting in mm-wave 5G networks is the precise estimation of rain attenuation for short-path links. The difficulties are further intensified in the tropical areas where the rainfall rate is very high. Different models are proposed to predict rain attenuation, however recent measurements show huge discrepancies with predictions for shorter links at mm-wave. The path reduction factor is the main parameter in the prediction model for predicting total attenuation from specific rain attenuation. This study investigates four path reduction factor models for the prediction of rain attenuation. A comparison was made between these models based on rain attenuation data measured at 26 GHz at 300 m and 1.3 km links in Malaysia. All models are found to predict rain attenuation at a 1.3 km link with minimum errors, while tremendous discrepancies are observed for 300 m link. Hence it is highly recommended to further investigate the reduction factor model for shorter links less than 1 km